Perancangan Aplikasi Peta Digital (CarryMap) Guna Optimalisasi Pengelolaan Data Di BPP Kecamatan Sinjai Utara Kabupatesn Sinjai Provinsi Sulawesi Selatan - widya ningsih ningsih (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2021)
Abstrack Data as a source of information is very important to support the developmentof sustainable agriculture. The obstacle that is experienced the most by the Department of Agriculture is the availability of information systems of agricultural data that are not up to date. CarryMap is an application that is used to display a land distribution mapand also information without enclose data in the form of shape files or the other data.This study aims to 1) describe the existence of agricultural potential data in the BPP of North Sinjai,Sinjai; 2) describe the mechanism of data collection used in North Sinjai; 3)design an application of digital map for data management existed in North Sinjaito make the application becomes more effective; 4)describe the implementation of the digital map application based on geographic information systems of North Sinjai; 5) describe the use of data as the information of agricultural development. This study is a descriptive study with a qualitative approach. The main techniques in collecting data are document study and in-depth interviews. The results showed that the dataof agricultural potential was still not organizedwell because the mechanism of data collection was still done manually. The application design went through several stages but the implementation of the application design was well responded by the agricultural extensions. The use of data as a source of information on agricultural development must have a potential data of land resourcein detail. Keywords : CarryMap, Data, Digital Map